CDK9: A Comprehensive Review of Its Biology, and Its Role as a Potential Target for Anti-Cancer Agents - Anshabo, Abel Tesfaye; Milne, Robert; Wang, Shudong; Albrecht, Hugo (Frontiers in Oncology, 2021)
Cyclin-dependent kinases (CDKs) are proteins pivotal to a wide range of cellular functions, most importantly cell division and transcription, and their dysregulations have been implicated as prominent drivers of tumorigenesis. Besides the well-established role of cell cycle CDKs in cancer, the involvement of transcriptional CDKs has been confirmed more recently. Most cancers overtly employ CDKs that serve as key regulators of transcription (e.g. CDK9) for a continuous production of short-lived gene products that maintain their survival. As such, dysregulation of the CDK9 pathway has been observed in various haematological and solid malignancies, making it a valuable anticancer target. This therapeutic potential has been utilized for the discovery of CDK9 inhibitors, some of which have entered human clinical trials. This review provides a comprehensive discussion on the structure and biology of CDK9, its role in solid and haematological cancers, and an updated review of the available inhibitors currently being investigated in preclinical and clinical settings.